Bioelectrofuel synthesis by nanoenzymes : novel alternatives to conventional enzymes - Singh, Lakhveer; Rana, Supriyanka; Thakur, Sveta; Pant, Deepak (Elsevier Ltd, 2020)
Recent bioinspired efforts of designing novel nanoenzyme-based electrocatalysts are driven by the urgency of making bioelectrofuels more affordable and efficient. Unlike natural enzymes, nanoenzyme-modified electrodes with large surface areas enclose numerous biomimicking active sites to facilitate enhanced microbial growth followed by increased reactant-to-bioelectrofuel conversion.